1995
DOI: 10.1007/bf00200324
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio total energy study of brucite, diaspore and hypothetical hydrous wadsleyite

Abstract: Abstract. Ab initio total energy calculations based on the local density approximation (LDA) and the generalised gradient approximation (GGA) of density functional theory have been performed for brucite, Mg(OH)2, diaspore, A1OOH and hypothetical hydrous wadsleyite, Mg7Si4O14(OH)a. The use of a general gradient approximation (GGA) is essential to obtain a good agreement (~ 1%) of the calculated lattice parameters to diffraction data. The calculated fractional coordinates of brucite and diaspore are in good agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
0
34
1
Order By: Relevance
“…Early studies on bulk AEMHs revealed that the application of temperature and pressure may result in dramatical changes in their crystal structure and their electronic properties [11][12][13][14][15][16][17][18]. Moreover, early theoretical studies showed the reliability of the use of first principles calculations with a plane-wave basis set in combination with the generalized gradient approximation exchange-correlation functional for the investigation of structural and electronic properties of these materials [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies on bulk AEMHs revealed that the application of temperature and pressure may result in dramatical changes in their crystal structure and their electronic properties [11][12][13][14][15][16][17][18]. Moreover, early theoretical studies showed the reliability of the use of first principles calculations with a plane-wave basis set in combination with the generalized gradient approximation exchange-correlation functional for the investigation of structural and electronic properties of these materials [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…From the theoretical side, in the focus were mainly structural, vibrational and chemical properties. 32,33 Recent studies on the electronic structure were undertaken primarily to understand novel opto-electronic properties of Mg(OH) 2 :C films.…”
Section: Introductionmentioning
confidence: 99%
“…Then, he proposed a hypothetical structure of hydrous wadsleyite [Smyth, 1994]. The proposed defect structure was studied by quantum mechanical simulations [Winkler et al, 1995]. The stability of protonated O1 site in wadsleyite was confirmed by ab initio molecular dynamics [Haiber et al, 1997] and interatomic model potential calculations [Walker et al, 2006].…”
Section: Introductionmentioning
confidence: 99%